The Portrait of Teacher Talk and Language Choices in EFL Classroom: Insights for Children’s Language Learning - Khusna, Khaula Amelia; Mustofa, Mutmainnah; Alka, Wensi; Ubaidillah, M. Faruq; Lee , Huan Yik; Putra, Suatmo Pantja (Jurnal Pendidikan Anak, 2022)
The present study focused on teachers’ perceptions of how teacher talk works in the classroom and some challenges they might encounter during initiating interaction to encourage students. A classroom observation was done to portray the data of the learning process and teachers’ interview was also conducted to discover insights about teacher talk and the challenges encountered in the classroom interaction. Findings demonstrated that the teachers enacted dominant English communication as the input rather than using students’ first language. They felt increasing the use of the target language would be more challenging as it is influenced by some aspects from both teachers and students’ motivation, attitude, and proficiency. In addition, teacher talk is varied in some extents based on the teacher and student factors. The findings also showed that teacher talk mostly occurred in the form of asking questions, giving directions, explaining the lesson, and praising the students. In addition, as the students were considered young learners, it was found that classroom interaction and language choice must be adjustable in order to make communication become more effective. Keywords: teacher talk, perception, challenge, language choice, primary level